Isolation of adult porcine islets of Langerhans. - Toso, C; Brandhorst, D; Oberholzer, J; Triponez, F; Bühler, L; Morel, P (2000)
While human islet allotransplantation is limited due to the shortage of donors, pig islet xenotransplantation appears to be a possible alternative. Enzymatic digestion is the method most commonly used for adult pig islet isolation, but since the description of the semiautomated isolation technique in the late 1980s, yields of pig islet isolations have not increased significantly. This review article is intended to collate published information on adult pig islet isolation to provide the reader with a clear overview of the relevant issues in this field, and to detail the current state of the art.